Pengaruh Bid-Ask Spread, Market Value dan Dividend Payout Ratio Terhadap Holding Period pada Perusahaan Jakarta Islamic Index Periode 2017-2019 - Muhammad Kurniawan; Ersi Sisdianto; Ulul Azmi Mustofa (Jurnal Ilmiah Ekonomi Islam, 2022)
The capital market is an alternative investment for investors. The advantages that can be had in stock investment are the increase in stock prices (capital gains) and dividends. Investors can maximize profits by analyzing the right time to hold or release their assets. Determining the ownership period or holding period is an important consideration for investors in determining investment strategy decisions to achieve certain goals. Investors has their own investment analysis in determining the period of share ownership or holding period. This study aims to determine the effect of the bid-ask spread, market value, and dividend payout ratio variables on the holding period. This research uses quantitative research with descriptive approach. The population of this study are companies listed in the Jakarta Islamic Index (JII) for the 2017-2019 period. The sampling technique used in this research is purposive sampling technique. The sample companies in this study are 15 companies. The data processed is secondary data obtained by researchers through daily and annual reports from the official website of the Indonesia Stock Exchange and the official websites of related companies. The data analysis method used is multiple linear regression analysis with the help of SPSS 23 program. The results of this study indicate that simultaneously the bid-ask spread, market value, and dividend payout ratio variables have a significant effect on the holding period. Partially, the market value and dividend payout ratio variables have a positive and significant effect on the holding period, while the bid-ask spread variable has no significant effect on the holding period.